An integrated study (geochemistry, stable oxygen and carbon isotopes, nannofossils, planktonic foraminifera, inoceramid bivalves, ammonites and crinoids) of the Waxahachie Dam Spillway section, north Texas: a possible boundary stratotype for the base of the Campanian Stage - Gale, A; Hancock, J; Kennedy, W; Petrizzo, MR; Lees, J; Walaszczyk, I; Wray, D (Cretaceous Research, 2016)
The spillway of Lake Waxahachie, Ellis County (Texas), exposes a >17 m section of the Hutchins Member of the Austin Chalk Group, unconformably overlain by Taylor Clay. The Austin sequence was regarded as a potential Global Stratotype Section for the base of the Campanian Stage at the 1995 Brussels meeting on Cretaceous Stage boundaries, with the last occurrence of the crinoid Marsupites testudinarius (von Schlotheim, 1820) as the potential boundary marker. An integrated study of the geochemistry, stable carbon and oxgen isotopes, nannofossils, planktonic foraminifera, inoceramid bivalves, ammonites and crinoids of this section place the last occurrence of M. testudinarius in a matrix of eighteen ancillary biostratigraphic markers, while the boundary can also be recognised on the basis of a δ13C excursion that can, in principle, be detected globally in marine sediments. A new forma of the crinoid Marsupites testudinarius is introduced. The Waxahachie section fulfils sufficient geological criteria as to be an excellent candidate GSSP for the base of the Campanian Stage, if problems of ownership and access to the section can be resolved. © 2007 Elsevier Ltd. All rights reserved.